2013
DOI: 10.1080/10962247.2013.790856
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of emissions and removal of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) at start-up periods in a hazardous waste incinerator

Abstract: A study was conducted to observe the changes in polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/F) levels and congener profiles in the flue gas of a hazardous waste incinerator during two start-up periods. Flue gas samplings were performed simultaneously through Air Pollution Control Devices (APCDs) (including boiler outlet, electrostatic precipitator (ESP) outlet, wet scrubbers (WS) outlet, and activated carbon (AC) filter outlet) in different combustion temperatures during a planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Results showed that PCDD/Fs are removed primarily by wet scrubbers and ESP, while PCDD/F removal rate of the scrubbers is slightly higher than that of ESP. Higher removal efficiency of the Downloaded by [New York University] wet scrubbers (which was confirmed by the flue gas measurements made at the inlet and outlet of the scrubbers during the start-ups in Karademir and Korucu (2013)) could be explained by the removal of some gaseous fraction in the lime scrubber, in addition to the removal of particulate fraction in the scrubbers. On the other hand, PCDD/F analyses in the flue gas through APCE during the start-ups indicated that some PCDD/F formation may occur in ESP (possibly by de novo synthesis), leading to an increase in the gaseous fraction of PCDD/Fs through ESP.…”
Section: Mass Fluxesmentioning
confidence: 60%
See 1 more Smart Citation
“…Results showed that PCDD/Fs are removed primarily by wet scrubbers and ESP, while PCDD/F removal rate of the scrubbers is slightly higher than that of ESP. Higher removal efficiency of the Downloaded by [New York University] wet scrubbers (which was confirmed by the flue gas measurements made at the inlet and outlet of the scrubbers during the start-ups in Karademir and Korucu (2013)) could be explained by the removal of some gaseous fraction in the lime scrubber, in addition to the removal of particulate fraction in the scrubbers. On the other hand, PCDD/F analyses in the flue gas through APCE during the start-ups indicated that some PCDD/F formation may occur in ESP (possibly by de novo synthesis), leading to an increase in the gaseous fraction of PCDD/Fs through ESP.…”
Section: Mass Fluxesmentioning
confidence: 60%
“…Since Startup-1 was a long start-up performed in a period of 136 h, residence time of the flue gas in the temperature window of PCDD/F formation by de novo synthesis (i.e., about 400-250 • C) in the cooling zone (including boiler) should be higher in Startup-1, which may lead to higher formation rates of PCDD/F by catalytically heterogeneous synthesis on fly ash surfaces in the boiler and ESP (Eduljee and Cains, 1996;Lu et al, 2007). High furan/dioxin (F/D) ratios observed both in the boiler fly ash (about 2.5) and in the flue gas leaving the boiler (especially in the particle-bound phase, which is about 4.5, given in Karademir and Korucu (2013)) support the heterogeneous de novo synthesis assumption (Chi et al, 2005;Wang et al, 2007).…”
Section: Mass Fluxesmentioning
confidence: 97%
“…PCDD/Fs are generally formed due to incomplete combustion at the related emission sources [23][24][25][26][27]. Several recent studies have focused on the high PCDD/F emissions during the start-up of MSWIs [28][29][30][31][32][33][34][35][36]. These elevated PCDD/F concentrations remain at high levels even 18 h after the injection of activated carbon (AC) during the start-up process [37].…”
Section: Introductionmentioning
confidence: 99%
“…Start-up procedures have been shown to be significant and important periods in terms of PCDD/F emissions during incinerator operations (Tejima et al, 2007;Wang et al, 2007;Karademir and Korucu, 2013;Lin et al, 2014). According to Wang et al (2007) and Karademir and Korucu (2013), the PCDD/F emissions during start-up procedures could be 2-4 times higher than those of the whole year normal operations (Cheruiyot et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to Wang et al (2007) and Karademir and Korucu (2013), the PCDD/F emissions during start-up procedures could be 2-4 times higher than those of the whole year normal operations (Cheruiyot et al, 2016). The elevated PCDD/F emissions during start-up procedures of incinerators have been attributed to incomplete combustion of diesel and feeding wastes, state of cleaning of boiler section as well as furnace temperature passing through PCDD/F formation window inevitably (Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%